Parents' Needs and Their Perceived Obstacles With Team Members in Perinatal Palliative Care: A Qualitative Phenomenological Study. Issue 6 (26th December 2022) - Yasar, Beril Nisa; Terzioglu, Fusun
Abstract : Advances in prenatal diagnosis have made medical, psychological, and ethical issues regarding the diagnosis of fetal anomalies a crucial topic of research. This study identified the needs of parents of unborn babies with fetal anomalies and their views regarding the services of interdisciplinary team members in charge of assisting them. The sample consisted of 30 parents and 40 team members from a women's health education and research hospital. Data were collected through face-to-face interviews and were qualitatively analyzed using the phenomenological method of interpretation. The results showed that parents' physical, psychological, social, and spiritual needs during pregnancy, childbirth, and postpartum were not fully met after their unborn babies were diagnosed with fetal anomalies. The results also showed that team members needed a structured program, legal regulations, and training to provide holistic care.